Protecting the Body in War and Combat Metal Body Armour in Bronze Age Europe - Mödlinger, Marianne (Verlag der Österreichischen Akademie der Wissenschaften, 2018)
This monograph provides an overview of all metal body armour from the European Bronze Age from a typo-chronological perspective but also in focusing on the manufacture and usage of such armour. This was enabled through the re-evaluation of central and eastern European finds in particular and their material analyses. The research history, distribution and chronology, as well as manufacture and use of helmets, greaves and cuirasses is discussed.